Occupational exposure to HIV: a conflict situation for health workers - Kumakech, E.; Achora, S.; Berggren, V.; Bajunirwe, F. (International Nursing Review, 2011)
Aim: To determine the frequency of occupational exposure to human immunodeficiency virus (HIV), the circumstances and predisposing factors, the high-risk groups, the extent to which exposures are reported and the post-exposure prophylaxis (PEP) utilized by health-care workers (HCWs) and students in a Ugandan hospital. Background: Occupational exposure to HIV is a low but potential risk of HIV infection to health workers. Method: Self-administered questionnaire was given to 224 participants (including 98 HCWs and 126 students) in Mbarara Hospital, Uganda. Data were analysed with descriptive statistics using the Statistical Package for the Social Sciences version 15.0 (SPSS Inc, Chicago, IL, USA). Findings: Of the 224 participants surveyed, 19.2% reported having sustained injection needle stick injuries in the previous year, of which 4.46% occurred with HIV-infected blood. Other reported injuries were cannula needle stick injury (0.89%), suture needle stick injuries (3.13%), scalpel cut injuries (0.45%) and muco-cutaneous contamination (10.27%). The most affected groups were nurses–midwives for scalpel injuries and students for stick injuries. The predisposing factors reported included lack of protective devices and recapping of needles. Exposures were under-reported. Uptake of PEP was also low. Conclusion: Occupational exposure to HIV presents a conflict situation for HCWs. It remains a frequent occurrence particularly among student nurses–midwives, despite being avoidable. Its prophylactic treatment is hampered by poor reporting and investigation of exposures, and poor access to PEP. Strict adherence to auniversal precaution and proper handling of occupational exposure to HIV should be encouraged
Keywords: Health-Care Workers; HIV; Occupational Exposure; Post-Exposure Prophylaxis; Predisposing Factors; Students; Uganda